THE CONCEPT OF AEOS WITHIN THE CONTEXT OF THEORY OF LAW - M. A. Rylskaya; D. V. Nekrasov (Финансы: теория и практика)
Development of integration processes in the Customs Union (CU) of the Republic of Belarus, Kazakhstan and the Russian Federation at the present stage requires reshaping of customs administration in accordance with best practices and enforcement standards of the World Customs Organization. The legal institution of Authorized Economic Operator (AEO) is currently the subject of study of Russian and foreign researchers, due to the need to improve customs control through the use of modern tools and technologies designed for providing effective customs control and secure supply chain. The subject institution is based on introduced models of special customs simplifications (customs benefits) in exchange for compliance with economic operator specific requirements and conditions established by the customs legislation. In view of the forthcoming transformation of the Customs Union into the Eurasian EconomicUnion by2015,the AEO institution is acquiring new content and requires further study.To obtain the most objective data on the subject under examination the authors used general scientific methods, such as induction, deduction, analysis, synthesis. In addition, they used such particular scientific methods as comparative legal, historical legal, formal logic, system analysis, etc. In order to create an optimal balance between the rights and obligations of bona fide traders and the state represented by the customs authorities, the customs administration needs constant improvement. The authors exploring the AEO institution, come to the conclusion that its further development needs the improvement of special AEO status in terms of revising its administrative powers. This conclusion is based not only on the analysis of areas of concern related to the assignment of administrative and legal status to the AEO and its subsequent activities but also on the investigation into national AEO programs implemented by foreign customs administrations. The definition of the AEO legal institution is unquestionably has both theoretical and practical value; it constitutes a significant contribution to the theory of administrative law and customs law as well as to the practice of public administration.